Influence of psychological autonomy support of peer instruction: A novel interactive approach using Instagram in language learning - Alfadda, Hind; Afzaal, Muhammad; Mahdi, Hassan; Alaudan, Rasha; Curle, Samantha (Frontiers in Psychology, 2022)
This study seeks to investigate the impact of the use of just-in-time (JiT) teaching and peer instruction (PI) strategies on the promotion of students’ achievement, interaction and motivation in language learning. Students were recruited from the undergraduate TESOL program during the first semester of 2019 at University. A multiple method research design was used to address the research questions. First, a two-group quasi-experimental design was implemented. In the first group, a lecture-based strategy was used (n=28), while in the second group, JiT and PI strategies were used (n=27). A private Instagram account was created as a platform for the study. Second, focus group interviews were conducted to assess the students’ views about the use of Instagram as an educational tool in terms of its flexibility and usefulness. The findings of the study suggest that JiT teaching, and PI promoted students’ achievements and enhanced students’ motivation, particularly with regard to fluency and novelty in the second language. Furthermore, the students viewed Instagram as a successful educational tool that significantly facilitated their collaboration. However, the study highlighted some challenges of the use of JiT teaching and PI to facilitate language learning, especially in class discussions in which instructors perceived difficulty due to a lack of time. Finally, the study suggests that students must be provided with adequate e-learning tools to enhance motivation for language learning.